Milo stover, forage sorghum and alfalfa silages for growing heifers - K. Bolsen; Jack G. Riley; C. Grimes (Kansas Agricultural Experiment Station Research Reports, 1977)
Ninety heifer calves were used to compare six rations containing various combinations of milo stover, forage sorghum and alfalfa silages. In the 96-day trial, heifers fed 100% forage sorghum silage outperformed heifers fed 100% milo stover silage. Adding forage sorghum or alfalfa silage to the 100% milo stover silage ration improved rate and efficiency of gain. Observed gains and efficiencies for the 67% milo stover + 33% forage sorghum and for the 33% milo stover + 67% forage sorghum silage rations exceeded predicted gains and efficiencies an average of 10.7% and 11.5%, respectively.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen& #x27; s Day; 1977; Beef; Milo stover; Forage sorghum; Alfalfa silages; Heifers